Emerging issues and challenges in investigating the Malaysian Ponzi scheme investor: A qualitative pilot study - Bahyah, Abdul Halim; Syamsul Azri, Abdul Rahman; Muhammad Takiyuddin, Abdul Ghani (2019)
This article begins with discussing the significance of undertaking a pilot study in qualitative research, especially for hard-to-reach research population. Besides that, this paper also features the standard procedure in conducting a qualitative pilot investigation according to the available literature. To reiterate the advantages of pilot exercise, it outlines several methodological and practical consideration manifested during the pilot work, as well as the improvements made for the fieldwork study from the experiences and lessons throughout the pilot study. In the end, it recommends the employment of the pilot inquiry due to the advantages of exploring particular feasibility and methodological issues related to the process of conducting any form of qualitative research. Also, the authors call for more qualitative researchers to proclaim their pilot study so that the trustworthiness and transferability of the study could be improved.